Effect of the storage conditions on the microbiological and physicochemical qualities of shea butter - Honfo, Gbenato Fernande; Hell, Kerstin; AKISSOE, H. NOËL; COULIBALY, Ousmane; HOUNHOUIGAN, DJIDJOHO JOSEPH; FANDOHAN, Pascal (My University, 2011)
Storage conditions are key constraints for qualityassurance of the shea (Vitellaria paradoxa Gaertner) butter. Inthe Sudan savannah Africa, storage conditions of butterproduced by women vary across and among processors,traders and consumers. These conditions could impact thequality of the products and reduced their access to interna-tional market. The present study attempted to investigate theeffect of storage duration and packaging materials onmicrobiological and physicochemical characteristics of sheabutter under tropical climatic conditions. Five packagingmaterials traditionally used in shea butter value chain weretested for their efficacy in storing shea butter freshly produced.Total germs, yeasts and mould varied with packagingmaterials and storage duration. After 2 months of storage,moisture content of butter remained constant (5%) whereasacid value increased from 3.3 to 5.4 mg KOH/g, peroxidevalue from 8.1 to 10.1 meq O2/kg and iodine value droppedfrom 48.8 to 46.2 mg I2/100 g in shea butter irrespectively tothe storage materials used. The basket papered with jute bagwas the less effective in ensuring the quality of butter duringstorage while plastic containers and plastic bags seemed tobe the best packaging materials
Keywords: Shea butter.Packaging material.Acid value.Peroxide value.Iodine value